TECHNOLOGICAL DEVELOPMENTS ON PURCHASING DECISIONS IN THE TOKOPEDIA MARKETPLACE: Perkembangan Teknologi Terhadap Keputusan Pembelian di Marketplace Tokopedia - Agil Bagus Prasetyo; Herlinda Maya Kumala Sari (PT ANTIS INTERNATIONAL PUBLISHER, 2024)
This study aims to determine that e-service quality, e-money, and e-word of mouth simultaneously affect purchasing decisions. This research uses quantitative methods. Sampling uses non-probability sampling techniques and accidental sampling methods. There were 100 respondents involved in this study. Data collection using a questionnaire distributed via google form. And in data processing using the SPSS Statistic 16 program. This study found that e-service quality has a significant effect on purchasing decisions, e-money has a significant effect on purchasing decisions, and e-word of mouth has a significant effect on purchasing decisions in the Tokopedia marketplace.